On the need for bidirectional coupling of road traffic microsimulation and network simulation - Sommer, Christoph; Yao, Zheng; German, Reinhard; Dressler, Falko (Proceeding of the 1st ACM SIGMOBILE workshop on Mobility models - MobilityModels '08)

Progressing toward realistic mobility models in VANET simulations - Sommer, Christoph; Dressler, Falko (IEEE Communications Magazine)

Tomografische Ultraschallmessverfahren für die Prozessmesstechnik - Henning, Bernd

Editorial: XXI. Messtechnisches Symposium des Arbeitskreises der Hochschullehrer für Messtechnik (AHMT), Paderborn, 20.--22.09.2007 - Henning, Bernd (Technisches Messen)

Verfahren zur Bestimmung einer Eigenschaft eines strömenden Mediums sowie Ultraschallzähler - Henning, Bernd

Separation und Bewertung verschiedener Moden der Schallausbreitung im akustischen Wellenleiter - Rautenberg, Jens; Henning, Bernd
In this contribution it is shown that the modal components of the received signal at the end of an acoustic waveguide can be suppressed or intensified if the two electrodes of a piezo-electric ceramic are shaped in a special way. With this it is possible to measure different signals which can be used to differ between the liquids dissipation and the signal attenuation caused by the waveguide geometry as well as impedance conditions. With the help of the principal component analysis it should be possible to infer the modal amplitudes from the received signals of one ultrasonic transducer and to calculate the acoustic impedance of the liquid that is included in the wave guide.

Simultaneous direct and indirect measurement of sound velocities - Rautenberg, Jens; Henning, Bernd
This contribution is about different types of sonagram processing and their application for the simultaneous direct and indirect measurement of both the longitudinal and the transversal ultrasound velocities of highly absorbing isotropic synthetic polymers. Therefore, the pulse transmission of an initially longitudinal wave through a hollow cylindrical specimen is investigated experimentally and theoretically.

Piezosensor zur Temperaturmessung - Rautenberg, Jens; Ziegler, Horst; Gaugler, Ulrich; Dietz, Gerhard; Unverzagt, Carsten; Kehl, Romina; Henning, Bernd

Verfahren zur Bestimmung einer Eigenschaft eines strömenden Mediums - Rautenberg, Jens; Ziegler, Horst; Gaugler, Ulrich; Dietz, Gerhard; Unverzagt, Carsten; Kehl, Romina; Henning, Bernd

Block Model: an educational model of program comprehension as a tool for a scholarly approach to teaching - Schulte, Carsten (ICER)

Duality Reconstruction - Teaching Digital Artifacts from a Socio-technical Perspective - Schulte, Carsten (ISSEP)

What are information technology's key qualifications? - Dörge, Christina; Schulte, Carsten (ITiCSE)

Digitale Artefakte und Schlüsselkompetenzen im Informatikunterricht der Sekundarstufe I - Schulte, Carsten; Dörge, Christina (DDI)

Weighted voting as approximate MAP prediction in pairwise classification - Hüllermeier, Eyke; Vanderlooy, S. (In Proceedings Workshop LWA-2008, Lernen-Wissensentdeckung-Adaptivität, Würzburg, Germany)

Evolutionary construction of multiple graph alignments for mining structured biomolecular data - Fober, T.; Hüllermeier, Eyke; Mernberger, M. (In Proceedings Workshop LWA-2008, Lernen-Wissensentdeckung-Adaptivität, Würzburg, Germany)

Evolutionary construction of multiple graph alignments for the structural analysis of biomolecules - Fober, T.; Hüllermeier, Eyke; Mernberger, M. (iIn Proceedings GCB-2008, Germany Conference on Bioinformatics, Dresden 2008)

Internationalisierung, Unternehmensgröße und Konzernsteuerquote - Bischoff, Dennis; Halberstadt, Alexander; Sureth, Caren

Income-Related Minimum Taxation Concepts and Their Impact on Corporate Investment Decisions - Dahle, Claudia; Sureth-Sloane, Caren

arqus-Stellungnahme zur notwendigen Reform der Abgeltungssteuer - Kiesewetter, Dirk; Niemann, Rainer; Hundsdoerfer, Jochen; Knirsch, Deborah; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Der Betrieb)

arqus-Stellungnahme: Das BilMoG - Eine Chance zur Steuervereinfachung? - Knirsch, Deborah; Müller, Heiko; Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Deutsches Steuerrecht)

The Impact of Thin Captialization Rules on Shareholder Financing - Maßbaum, Alexandra; Sureth-Sloane, Caren

Unternehmensbewertung für substanzsteuerliche Zwecke - Eine empirische Analyser des Stuttgarter Verfahrens und alternative Ansätze - Müller, Jens; Sureth-Sloane, Caren

Steuern und Risiko als substitutionale oder komplementäre Determinanten unternehmerischer Investitionspolitik? - Niemann, Rainer; Sureth-Sloane, Caren

Auswirkungen einer Reform des Erbschaft- und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens- und Grundvermögen - Sureth-Sloane, Caren; Müller, Jens; Houben, Henriette; Maiterth, Ralf (Untrnehmensbesteuerung 2008: Neue Wege gehen)

Kritische Anmerkungen zur Ermittlung des tatsächlichen Werts einer Familienpersonengesellschaft nach neuer Rechtslage - Sureth-Sloane, Caren; Nordhoff, Daniel (Der Betrieb)

Praxisnähe und universitäre Ausbildung: Fallstudie der Universität Paderborn - Sureth-Sloane, Caren; Nordhoff, Daniel (DATEV BILDUNGSforum)

Proposals for a European Corporate Taxation and Their Influence on Multinationals' Tax Planning - Sureth-Sloane, Caren; Üffing, Michaela

Neural networks in 3D medical scan visualization - Zukic, D.; Elsner, A.; Avdagic, Z.; Domik, Gitta (Proceedings of 11th International Conference on Computer Graphics and Artificial Intelligence)

Navigierbare Kompression von XML-Datenströmen - Hartel, Rita

Detecting Suspicious Relational Database Queries - Böttcher, Stefan; Hartel, Rita; Kirschner, Matthias (Third International Conference on Availability, Reliability and Security)

BSBC: Towards a Succinct Data Format for XML Streams - Böttcher, Stefan; Hartel, Rita; Heinzemann, Christian (WEBIST 2008, Proceedings of the Fourth International Conference on Web Information Systems and Technologies)

Compressing XML Data Streams with DAG+BSBC - Böttcher, Stefan; Hartel, Rita; Heinzemann, Christian (Web Information Systems and Technologies, 4th International Conference, WEBIST 2008, Revised Selected Papers)

Ultraschall-Messtechnik und Ultraschall-Tomografie - Henning, Bernd

Development status and market potential of hot formed ballistic steels - Tröster, Thomas; Howe, C.; Müller, M.; Rostek, W.

The Effect of Texture on the Fatigue Properties of Ultrafine-Grained Interstitial-Free Steel - Niendorf, Thomas; Marten, Thorsten; Maier, Hans J.; Karaman, Ibrahim (Materials Science Forum)
The present paper reports on the effect of texture on the cyclic stress-strain response (CSSR) and the fatigue life of ultrafine-grained (UFG) interstitial-free (IF) steel. Tests in the lowcycle fatigue (LCF) regime were conducted on material that was processed by the equal channel angular extrusion (ECAE) technique along the so called “efficient” route 8E. This route has been shown to result in a homogeneous microstructure with a high fraction of high angle grain boundaries (HAGBs), which are beneficial for a stable CSSR. In addition, the evolution of the microstructure was characterized by means of electron optical techniques, including electron backscattered diffraction, and by X-Ray diffractometry. It was found that the initial texture of specimens cut from the ECAE billet along different orientations with respect to the extrusion direction (ED) has a substantial effect on the CSSR of the UFG IF steel. Furthermore, microscopy results indicated the notable influence of the last ECAE processing step on the evolution of damage in the material.

Is an ordinal class structure useful in classifier learning? - Hühn, J.; Hüllermeier, Eyke (International Journal of Data Mining, Modeling and Management)

Label ranking by learning pairwise preferences - Hüllermeier, Eyke; Fürnkranz, J.; Cheng, W.; Brinker, K. (Artificial Intelligence)

A critical analysis of variants of the AUC - Vanderlooy, S.; Hüllermeier, Eyke (Machine Learning)

Multilabel classification via calibrated label ranking - Fürnkranz, J.; Hüllermeier, Eyke; Mencia, E.; Brinker, K. (Machine Learning)

Learning valued preference structures for solving classification problems - Hüllermeier, Eyke; Brinker, K. (Fuzzy Sets and Systems)

Case-based learning in a bipolar possibilistic framework - Beringer, J.; Hüllermeier, Eyke (International Journal of Intelligent Systems)

Granular computing in machine learning and data mining - Hüllermeier, Eyke (Handbook on Granular Computing)

Ein verfeinertes elektrisches Modell für Teilchentreffer und dessen Auswirkung auf die Bewertung der Schaltungsempfindlichkeit - Coym, Torsten; Hellebrand, Sybille; Ludwig, Stefan; Straube, Bernd; Wunderlich, Hans-Joachim; G. Zoellin, Christian
Keywords: WORKSHOP

Testen mit Rücksetzpunkten - ein Ansatz zur Verbesserung der Ausbeute bei robusten Schaltungen - Amgalan, Uranmandakh; Hachmann, Christian; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Research Note: Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Research Note—Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Multimedia Production with a Content HUB Environment. Media Engineering for Mobile Computing Courseware - Herzog, Michael A.; Trier, Matthias (2007 4th IEEE Workshop on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications)

SCORM (Shared Content Object Reference Model) - Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Workflow-Modellierung - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Systemanalyse - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)